Low-cost Antenna Positioning System Designed with Axiomatic Design - Timothy Foley Joseph; Omelianov Vladimir; Koziel Slawomir; Bekasiewicz Adrian (MATEC Web of Conferences, 2017)
The Engineering Optimization and Modeling Center at Reykjavik University has been carrying out research on antenna CAD, including the simulation-driven design of novel antenna topologies. However, simulation is not enough to validate a design: a custom RF anechoic chamber has been built to quantify antenna performance, particularly in terms of field properties such as radiation patterns. Such experiments require careful positioning of the antenna in the chamber accurately in 3-axis with a short development time, challenging material constraints, and minimal funding. Axiomatic Design Theory principles were applied to develop an automated 3-axis positioner system for a reference antenna and the antenna to be calibrated. Each axis can be individually controlled with a repeatability of 1 degree. This 3000 USD device can be fabricated using easily available components and rapid prototyping tools.